Pengaruh Return on Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR) dan Price Earning Ratio (PER) Terhadap Harga Saham Perusahaan Sub Sektor Kosmetik & Keperluan Rumah Tangga Pada Bursa Efek Indonesia Periode 2016 – 2020 - Adang Djatnika Effendi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2022)
The purpose of this study was to determine the partial and simultaneous effect and significance of Return On Assets, Debt to Equity Ratio, Current Ratio and Price Earning Ratio on stock prices in cosmetics & household goods sub-sector companies on the IDX for the period 2016 – 2020. This study used the method descriptive and verification with a quantitative approach and sourced from secondary data, using a purposive sampling technique. Data collection uses documentation and literature study techniques. Preliminary data processing with Microsoft Excel 2016 assisted by using E-views 12 software. In estimating the panel data regression, the best model was chosen, namely the Fixed Effect Model. The results of the research variable Return On Assets do not have a significant positive effect on stock prices, the Debt to Equity Ratio and Current Ratio have a significant negative effect on stock prices and the Price Earning Ratio has a negative and insignificant effect on stock prices. While the results of the study simultaneously the variables Return On Assets, Debt to Equity Ratio, Current Ratio and Price Earning Ratio have an effect and can explain significantly as much as 96% of stock prices based on the value of the coefficient of determination. Tujuan penelitian ini untuk mengetahui pengaruh dan signifikan secara parsial maupun simultan Return On Asset, Debt to Equity Ratio, Current Ratio dan Price Earning Ratio terhadap harga saham pada perusahaan sub sektor kosmetik & keperluan rumah tangga di BEI periode 2016 – 2020. Penelitian ini menggunakan metode deskriptif dan verifiktif dengan pendekatan kuantitatif serta bersumber pada data sekunder, dengan menggunakan teknik purposive sampling. Pengumpulan data menggunakan teknik dokumentasi dan studi kepustakaan. Pengolahan data awal dengan microsoft excel 2016 dibantu menggunakan software E-views 12. Estimasi pada regresi data panel terpilihlah model terbaik yaitu Fixed Effect Model. Hasil penelitian secara variabel Return On Asset tidak berpengaruh positif signifikan terhadap harga saham, Debt to Equity Ratio dan Current Ratio berpengaruh negatif signifikan terhadap harga saham dan Price Earning Ratio berpengaruh negatif dan tidak signifikan terhadap harga saham. Sedangkan hasil penelitian secara simultan variabel Return On Asset, Debt to Equity Ratio, Current Ratio dan Price Earning Ratio berpengaruh dan dapat menjelaskan secara signifikan sebesar 96% terhadap harga saham berdasarkan nilai koefisien determinasi.